2009
DOI: 10.1002/hec.1458
|View full text |Cite
|
Sign up to set email alerts
|

An instrumental variables evaluation of the effect of antidepressant use on employment among HIV‐infected women using antiretroviral therapy in the United States: 1996–2004

Abstract: SUMMARYDepression is a common condition among patients with HIV. This paper uses panel data for 1,234 participants from the Women's Interagency HIV Study (WIHS) to estimate the effect of antidepressant use on the likelihood of being employed among women receiving highly active antiretroviral therapy (HAART) in the United States from 1996 to 2004. We show that naïve regressions of antidepressant use on employment generally result in negative or non-significant coefficients, whereas the instrumental variables ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Treatment of depression could lead to better quality of life, an improvement in underlying inflammation, and better outcomes for HIV and other related comorbidities, also affected by depression [38, 39]. Use of antidepressants in women with HIV on antiretroviral therapy was associated with a 29% higher rate of being employed [40]. Nonetheless, Cook et al recently reported that less than half of HIV infected women in WIHS with depressive symptoms actually received appropriate treatment [41].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of depression could lead to better quality of life, an improvement in underlying inflammation, and better outcomes for HIV and other related comorbidities, also affected by depression [38, 39]. Use of antidepressants in women with HIV on antiretroviral therapy was associated with a 29% higher rate of being employed [40]. Nonetheless, Cook et al recently reported that less than half of HIV infected women in WIHS with depressive symptoms actually received appropriate treatment [41].…”
Section: Discussionmentioning
confidence: 99%
“…Their omission could bias our results since we are not directly controlling for them (Wooldridge 2010, chapter 4). Moreover, there could be reverse causality because PLHIV with low adherence to ART are not likely to achieve adequate CD4 cell count and viral suppression, which in turn will have employment and earnings repercussions (Auld, 2002; Galárraga et al, 2010; Goldman, 2003), which could also affect housing.…”
Section: Methodsmentioning
confidence: 99%
“…More specifically, therapeutic advances increased the probability of maintaining employment or finding a new one, although there were still significant differences between the employment rates of the people living with HIV and those of the general population [17]. The existing literature is consistent with respect to the improvements in the employment status of people living with HIV over the past two decades, although, depending on the country and on the period on which the analyses are focused, there are certain variations due to the different progress of the treatments and the different socio-employment conditions in the countries where the analyses were performed [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 70%